« Dites ce que je dis, ne dites pas ce que je vous dis de dire » ? Dilemmes et paradoxes de l’activité discursive et métadiscursive dans l’enseignement et l’apprentissage de l’oral en langues étrangères - Robert Bouchard (Recherches en Éducation)
This article deals with the teaching of oral expression, a central target in foreign language classes. In these classes speaking is at the same time a teaching tool and the aim of learning. But for the native teacher in particular, “embodied” oral expression largely escapes conscious control. There can be big differences between what he wants to teach and what he “displays” naturally in his own oral expression in class. It is these manifestations of authentic speech that this study attempts to observe, by comparing them to learner speech but also to epi/metalinguistic comments made by the teacher. To do this, we shall analyse different moments of a foreign language French class, in France, designed for foreign students and taught by a native teacher (Corpus LiYan 2007